Anti-racist Text and Talk: A Critical Discourse Studies Approach to Black Feminism - Limerick, Philip P. (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2021)
While racist discourse has received much attention in Critical Discourse Studies (CDS), there is a dearth of scholarship on the anti-racist text and talk. A critical observation is that the anti-racist movement, and hence, discourse, often exclude women. With the goal of contributing to this gap in the CDS literature, the current analysis examines Black women's discourses concerning anti-Black racism in general and Black Feminism in particular. Four YouTube videos that feature both conference talks and news programs surrounding the topic of Black Feminism are analysed for recurring themes using thematic analysis and discourse structures from the perspective of critical discourse analysis. Findings reveal that the primary themes that emerged are the inclusion of Black women, Police brutality and unaccountability, and Black Feminism Defined, with various subthemes. In addition, the discourse structures examined are lexical choice, presupposition, pronominal choice, and the use of tag questions, among others. This study serves to further our understanding of the linguistic manifestation of ideologies through discourse concerning anti-racism and Black Feminism.